Kebijakan Pengelolaan Keuangan Dan Akuntabilitas Pelaporan Dalam Upaya Penyusunan Laporan Keuangan BUMDes Sesuai SAK ETAP - Sulistyowati, Endah; Kristiawan, Agung; Setyawardani , Lydia; Dewi, Mega Arisia; Nugraheni, Ratna (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to analyze and evaluate the preparation of BUMDes financial reports that do not comply with the SAK ETAP. This research is qualitative research with a comparative descriptive. The research object is BUMDes which manages the service and trade sectors. The data collection technique involve conducting documentary interviews with eight informants related to service and trade business units, observations were made at the location of business units. Based on interviews we conducted with informants from each administrative unit and the BUMDes treasurer, those who prepare financial reports have not been able to fully implement them in accordance with SAK ETAP. Constraints are limited competent knowledge of accounting, not yet understanding, educational background in scientific disciplines not from the field of accounting and never taking part in training related to accounting processes for preparing financial reports. The analysis techniques use provide understanding and guidance on accounting policies in the accounting process supported by the use of the Microsoft Excel computer application based on SAK ETAP, Village Regulations, and the Memorandum of Association/ Articles of Association of the BUMDes. The results show that the socialization of understanding and accounting policy guidelines for BUMDes are enthusiastic and motivated, increasing knowledge about the procedures for preparing financial reports in accordance with SAK ETAP which is supported by the use of Microsoft Excel computer technology applications to understand Accounting Information System design models, making BUMDes potentially have skilled human resources in classifying accounts, making financial management more detail, efficient and able to prepare financial reports in accordance with the SAK ETAP.